Optimistic, but not in control: Life-orientation and the theory of mixed control - Diemo Urbig; Erik Monsen (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Why are some people more optimistic about their life than others? Literature on locus of control suggests that optimism is associated with the belief that one's life outcomes are controlled by internal factors, such as ability, instead of external factors, such as powerful others or chance. Furthermore, some authors suggest that internal control beliefs interact with self-efficacy beliefs regarding their effects on outcome expectancies and thus optimism. We argue that it is not only self-efficacy that interacts, but efficacy beliefs about external factors, too. We further hypothesize that the effect of perceiving internal rather than external control on dispositional optimism depends on the difference between efficacy beliefs regarding internal and external factors. Since people can influence other people to be helpful, i.e., take proxy control, but are unlikely to influence chance, we extend this internal-versus-external view and suggest that the difference between perceived control by others and perceived control by chance affect dispositional optimism. In fact, we hypothesize that the effect of perceiving that it is other people who are in control, rather than chance, depends on the difference between efficacy beliefs regarding others and chance. A first empirical survey-based test produces substantial support for our theory. This is the first time control-efficacy interaction effects are shown for dispositional variables and for the three-dimensional construct of locus of control. We replicate a gender effect on correlations of dispositional optimism with self-reported risk taking and observe a gender effect for one of our new hypotheses.
Keywords: D8; D83; D84; 330; Information; knowledge; uncertainty; search; learning; information and knowledge; communication; belief; expectations; speculations; Meinung; Lebensverlauf; Erwartungstheorie; Lernprozess; Persönlichkeitspsychologie; Schätzung; Deutschland